Avaliação da eficiência de docentes de mestrados acadêmicos de turismo utilizando Data Envelopment Analysis - Iury Teixeira de Sevilha Gosling (2019)
The objective of this thesis was to propose and test a model of evaluation of teaching performance related to the scientific production, based on the relative efficiency frontier for teachers of courses of Academic Master of Tourism of Brazil, considering the quadrennium 2013-2016. The research was descriptive, of a quantitative nature, using secondary data of 55 professors. The model had as inputs (1) the Experience in PhD years, (2) participation and / or coordination of Projects and (3) Mentored Dissertations and as output (4) the CAPES score in terms of articles published in periodicals. The Data Envelopment Analysis methodology was used to measure the relative efficiency of professors, usingthese variables. A product-oriented VRS study was conducted to maximize professors’ scores. As a result, there were 9 professors at the efficiency frontier. Efficient professors are a benchmark for improving the efficiency of others. This is an important contribution, so that there is a continuous improvement of the professors linked to the Master courses in Tourism, since the efficiency gain of them will certainly be reflected in the improvement of the courses and the scores received by the courses. Another contribution that can not be underscored is the novelty of the study, which filled a gap on the professor assessment of an area not yet studied in the academia, the courses of Master of Tourism in Brazil.